FORMULASI EKTSTRAK POLIHERBAL KOMBINASI EKSTRAK TULANG CEKER AYAM TERHADAP BAKTERI STAPILOCOCUS AUREUS - Joko Santoso; Heru Nurcahyo (Jurnal Ilmiah Manuntung, 2019)
The development of traditional plants as herbal medicines continues to be increased, especially in local use. Aloe vera (Aloe vera), bay leaf (Eugenia polyantha) and Turmeric Rhizome (Curcuma domestica Val) have compounds that function as antibacterial. Chicken claw bones play a role in accelerating the growth of skin cells, but it also has the potential as an antibacterial. This combination is expected to increase the work of medicinal ingredients in killing bacteria. The work method begins with the selection of herbal ingredients, dry sorting, wet sorting and slicing. Drying the sample using an oven at a temperature of 40 which is then pollinated and sieved with 100 mesh. Before macerated with 70% ethanol solvent 1:10 ratio, the sample was tested microscopically. The extract was made of three formulas and tested for antibacterial activity in Stapilococus aureus bacteria using the well method. The antibacterial activity in formula 1 was 7.1mm, Formula 2 was 8.7mm and formula 3 was 10.2mm. Experiments were also carried out on extracts without collagen extracts with better inhibitory results compared to polyherbal extract combinations of collagen extracts. This research proves that polyherbal extract from chicken claw collagen extract has the ability of antibacterial activity. Formula 3 has the best inhibition compared to formulas 1 and 2.